Student DVD to Accompany Operations Management - William J. Stevenson (McGraw-hill, 2002)
Berisi : Interactive Quizzes, Power Point Slide, Study Outlines, Excel Templates, Screencam Tutorials, Memo Writing Exercise, Advance Topics, Web Links, Visit the OMC, Visit the Online, Visit Learning Center, Video Clips.